2023
DOI: 10.3390/s23020627
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Low-Cost Electronic Nose with an Open Sensor Chamber: Application to Detection of Ciboria batschiana

Abstract: In the construction of electronic nose devices, two groups of measurement setups could be distinguished when we take into account the design of electronic nose chambers. The simpler one consists of placing the sensors directly in the environment of the measured gas, which has an important advantage, in that the composition of the gas is not changed as the gas is not diluted. However, that has an important drawback in that it is difficult to clean sensors between measurement cycles. The second, more advanced co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…In Figure 2 , one can see a photo of the electronic nose device used, together with two samples of measured grain in Petri dishes. Details of the electrical circuit [ 24 ] of the electronic nose and the construction of the sensor chamber and operation principle [ 25 , 31 ] were described in previous papers.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 2 , one can see a photo of the electronic nose device used, together with two samples of measured grain in Petri dishes. Details of the electrical circuit [ 24 ] of the electronic nose and the construction of the sensor chamber and operation principle [ 25 , 31 ] were described in previous papers.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Our article is an attempt to improve the custom-made, low-cost device further. The electronic nose device used in the reported experiment was described in previous papers, where the construction of the electric circuit [ 24 ] and sensor chamber [ 25 ] were proposed. The current experiment’s main novelty focuses on verifying the various patterns of the sensor temperature modulation profiles and their optimization, allowing for a reduction in the measurement time.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors [235,236] have reported on the practical utilization of eNose for palm tree disease detection. Borowik et al [237] reported on the successful utilization of eNose for the detection of Phytophtora in Quercus acorn and later, with an improved chamber, Ciboria batschiana [238]. The same group [237] introduced a low-cost detection procedure for phytopathogenic fungi.…”
Section: E-sensesmentioning
confidence: 99%
“…Electronic nose systems can be used in a wide range of applications such as agriculture [12][13][14][15][16][17], environmental monitoring [18][19][20], food [21][22][23][24][25][26], quality control [27][28][29][30][31], military [32][33][34], and medical applications [35][36][37][38][39][40][41][42] like pharmaceutical, biomedical, disease and illness early detection, cosmetics, and numerous scientific research domains.…”
Section: Introductionmentioning
confidence: 99%
“…The sensors' attributes must be specific for each volatile substance. The chemiresistive sensors are used in an integrated e-nose because of their straightforward electrical characteristics and interface circuitry [16][17].…”
Section: Introductionmentioning
confidence: 99%